ضوابط الاعتدال فى الإنفاق (Al-Qamar, 2020)
Money has been given a significant status in Islamic teachings for its vital role in economy as prime intermediary to promote trade and employment. Hard earned Ḥalāl money is difficult to spend, so Islam has taken certain measures to persuade its followers to spend money for self needs, necessities and even luxuries but in a moderate manner avoiding destructing it in extravagant expenditure. This paper studies the Islamic principles of moderation in spending. It finds that Muslims are not only allowed but demanded to spend money with generosity but it is within certain limits.
Keywords: Islam; Spending; Needs; Moderation